2021
DOI: 10.3390/cells10081935
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Pinball Machine of the Plasma Membrane Regulates Plant Growth—A New Paradigm

Abstract: Novel molecular pinball machines of the plasma membrane control cytosolic Ca2+ levels that regulate plant metabolism. The essential components involve: 1. an auxin-activated proton pump; 2. arabinogalactan glycoproteins (AGPs); 3. Ca2+ channels; 4. auxin-efflux “PIN” proteins. Typical pinball machines release pinballs that trigger various sound and visual effects. However, in plants, “proton pinballs” eject Ca2+ bound by paired glucuronic acid residues of numerous glycomodules in periplasmic AGP-Ca2+. Freed Ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…This review recapitulates recent significant progress in AGP biology represented by the molecular pinball machine of the plasma membrane that unifies proton pumps, AGPs and Ca 2+ signalling [50].…”
Section: Final Conclusionmentioning
confidence: 89%
“…This review recapitulates recent significant progress in AGP biology represented by the molecular pinball machine of the plasma membrane that unifies proton pumps, AGPs and Ca 2+ signalling [50].…”
Section: Final Conclusionmentioning
confidence: 89%
“…Receptor-like protein kinases (RLKs) are a large family of membrane proteins essential for reproductive development (Cui et al, 2022), and Ca 2+ is described as an important ion in the entire reproductive process and has also been related to the putative functions and mode of action of AGPs (Cheng et al, 2002;Lamport and Vaŕnai, 2013). A recent study clearly highlighted AGPs as essential players involved in novel molecular pinball machines of the plasma membrane controlling cytosolic Ca 2+ levels that regulate plant metabolism (Lamport et al, 2021). In addition, recent studies have revealed that the capacity of AGPs to bind Ca 2+ ions is conferred by GlcA residues in the AGPs sugar chains (Lopez-Hernandez et al, 2020;Pfeifer et al, 2020;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mutants of glucuronosyltransferases (GLCATs), responsible for the addition of glucuronic acid (GlcA) to the AGP sugar chains were developmentally defective due to the reduced Ca 2+ binding to GlcA residues of AGPs (Lopez-Hernandez et al, 2020;Zhang et al, 2020). Recently, a review by Lamport et al (2021) clearly points AGPs as essential players in controlling cytosolic Ca 2+ levels in the plasma membrane and regulating plant metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium is a crucial molecule in reproductive processes, and over the years the association between calcium and AGPs has been increasingly studied. A review from Lamport and collaborators highlighted AGPs as essential players involved in novel pinball machine-like structures in the plasma membrane controlling cytosolic calcium levels and regulating plant metabolism (Lamport et al, 2021). Given that many of the reproductive events are dependent on calcium oscillations, it is possible that some specific AGPs expressed throughout the reproductive tissues act in calcium-mediated signaling pathways (Figure 9) (Iwano et al, 2004(Iwano et al, , 2012.…”
Section: Galt25789 Mutant Agps Have Low Glucuronic Acid Contentmentioning
confidence: 99%